Effects of varying protein source and ammonium chloride inclusion on feedlot goat growth and carcass traits - Mortsolf, Taylor J.; Sorensen, Rachel J.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2018)
The objectives of this project were to determine the effects of varying protein source and acid source in the diets of feedlot goats assess growth and carcass traits. Adding Ammonium chloride to goat diets helps reduce the risk of urinary calculi. The hypothesis was that adding SoyPlus and SoyChlor to the diets would increase goat growth and carcass traits, while lowering the cost of feed compared to using SBM, DDGS, and ammonium chloride. To test this hypothesis, 75 goats were used and there were 5 treatments with 3 goats per pen, and 5 pens per treatment. The goats were housed at the Kansas State University Sheep and Meat Goat center. The 5 treatments were Negative Control (SBM); Positive Control (DDGS); SoyPlus; SBM + SoyChlor; SoyPlus + SoyChlor. The goats had self-feeders and had continuous access to fresh water daily. Weights and feed were gathered weekly on Fridays for the whole 42d experiment. The measurements were BW, ADG, ADFI, G: F and was calculated every 7 days. At the beginning BW was pretty scattered (p= 0.57) for the 5 different treatments. Overall there was no significant difference of goat growth during the experiment (p= 0.087). The G:F ratio also showed no significant difference (p=0.374). The highest G:F ratio being SBM + SoyPlus (p=0.656), compared to the other 4 treatments. These results show that adding SoyPlus and SoyChlor did not have a significant difference in goat growth or carcass traits. The cost of the feed is actually higher when you add in the SoyPlus and/or SoyChlor, making using SBM and ammonium chloride in the diet, the cheapest option.
Keywords: Fall 2018